2012
DOI: 10.1590/s2237-60892012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance and menstrual cycle: a literature review

Abstract: Approximately 80% of all women of reproductive age experience psychological and physical changes associated with the premenstrual phase. Cognitive alterations are among the most common complaints. In this context, studies have assessed cognitive performance across the menstrual cycle in healthy women and also in women with premenstrual syndrome (PMS). The main objective of the present study was to review the literature on cognitive function in different phases of the menstrual cycle in women of reproductive ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Studies that base menstrual cycle phase confirmation on counting days use different criteria to define the luteal and follicular phases (Souza et al, 2012). Epting and Overman (1998) as well as Phillips and Sherwin (1992) reported that all studies from this field should investigate the occurrence of anovulatory cycles, since only 62% of women in the 20-24 age groups ovulate in all menstrual cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that base menstrual cycle phase confirmation on counting days use different criteria to define the luteal and follicular phases (Souza et al, 2012). Epting and Overman (1998) as well as Phillips and Sherwin (1992) reported that all studies from this field should investigate the occurrence of anovulatory cycles, since only 62% of women in the 20-24 age groups ovulate in all menstrual cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Epting and Overman (1998) as well as Phillips and Sherwin (1992) reported that all studies from this field should investigate the occurrence of anovulatory cycles, since only 62% of women in the 20-24 age groups ovulate in all menstrual cycles. Because anovulatory cycles have been associated with absence of progesterone increases in the luteal phase, failing to detect for this data (or eliminate them from the analyses) would decrease the probability of detecting abnormalities across the menstrual cycle (Broverman et al, 1981;Souza et al, 2012). Despite this fact, better performance in the first segment of SJFT can be explained with the study of authors Nicklas, Hackney, and Sharp (1989), using biopsies of vastus lateralis muscle, found that glycogen repletion and therefore glycogen muscle content was greater during the luteal phase (LP).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Em uma revisão de literatura, Souza, Ramos, Hara, Stumpf, e Rocha (2012) identificam 27 estudos sobre o Transtorno Disfórico Pré-Menstrual (TDPM). Os estudos identificados evidenciam uma leve alteração no desempenho cognitivo em mulheres sadias ao longo do ciclo menstrual, obtendo menores pontuações na fase lútea.…”
unclassified